Comparison of outcomes between children ventilated in a non‐paediatric intensive care and a paediatric intensive care unit: A retrospective analysis - X L Jingxi; P Tinarwo; R Masekela; M Archary (African Journal of Thoracic and Critical Care Medicine, 2022)
Background. Lack of paediatric intensive care infrastructure, human resources and expertise in low- and middle-income countries (LMICs) often results in critically ill children being managed in non-intensive-care unit (ICU) settings. Objectives. To compare the mortality between critically ill patients who required ventilation for more than 24 hours in a non-paediatric ICU (PICU) setting v. those admitted directly to a PICU.